Adult Learning Theories in Context: A Quick Guide for Healthcare Professional Educators. (April 2019) - Mukhalalati, Banan Abdulrzaq; Taylor, Andrea
Background: Adult learning theories play a pivotal role in the design and implementation of education programs, including healthcare professional programs. There is a variation in the use of theories in healthcare professional education programs and this is may be in part due to a lack of understanding of the range of learning theories available and paucity of specific, in-context examples, to help educators in considering alternative theories relevant to their teaching setting. This article seeks to synthesize key learning theories applicable in the learning and teaching of healthcare professionals and to provide examples of their use in context. Method and results: A literature review was conducted in 2015 and 2016 using PubMed, Scopus, Web of Science, and ERIC academic databases. Search terms used identified a range of relevant literature about learning theories, and their utilization in different healthcare professional education programs. The findings were synthesized and presented in a table format, illustrating the learning theory, specific examples from health and medical education, and a very brief critique of the theory. Outcome: The literature synthesis provides a quick and easy-to-use summary of key theories and examples of their use to help healthcare professional educators access a wider range of learning theories to inform their instructional strategies, learning objectives, and evaluation approaches. This will ultimately result in educational program enhancement and improvement in student learning experiences.